On the development of ICT in Uzbekistan and its future prospects - Dadaboyev Dilshod; Jakbaraliyeva Durdona (Genius Journals, 2022)
In this article, we will focus on the statistics of ICT in Uzbekistan, its development and ICT in education. Over the last decade, Uzbekistan has paid great attention to the field of ICT. Nowadays, ICT is developing in many areas. The government is adapting to ICT. Substantial work has also been done on legislation. Our country closely cooperates with international institutions in the field of ICT. However, the further development of ICT requires a lot of effort. In this article, we will highlight the disadvantages, advantages and innovations related to ICT in our country and in our education system
Keywords: ICT of Uzbekistan; population of internet users; secure internet servers; fixed broadband subscriptions